The Impact Of Transformational Leadership And Psychological Empowerment On Organizational Citizenship Behaviors: A PLS-SEM Approach - Mohammed Abdulrab; Mohammed A. Alwaheeb; Yaser Hasan Salem Al-Mamary; Ali Al-Tahitah; Abdul Rahim Zumrah (Innovare Academics Sciences Pvt. Ltd, 2024)
Indexed by Scopus